Brain oscillations are highly influenced by gender differences - Güntekin, Bahar; BAŞAR, EROL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2007)
There are few studies describing gender differences in event related oscillations (EROS). In the present report we demonstrate that gender differences are apparent in EROS even during simple visual stimulation, possibly activating very basic sensory networks. The data of 32 (16 males) healthy subjects were recorded from thirteen different scalp locations (F-3, F-4, C-z, C-3, C-4, T-3, T-4, T-5, T-6, P-3, P-4, O-1, O-2). Analysis was performed in the delta (0.5-3.5 Hz), theta (5-8.5 Hz), alpha (9-13 Hz), beta (15-24 Hz), and gamma (28-48 Hz) frequency ranges. The results showed that the maximum peak-to-peak delta response amplitudes for women were significantly higher than for men over occipital, parietal, central and temporal electrode locations. There were also differentiations in the beta and gamma oscillatory responses. These gender differences were most pronounced over the electrode Site O-2, that is, over primary visual areas. It is suggested that this study might serve as a standard to investigate gender differences in electrophysiology. (c) 2007 Elsevier B.V All rights reserved.
Keywords: gender differences; brain oscillations; occipital cortex; EEG; visual evoked potentials; theta; potentials; dynamics; gamma; task; cinsiyet farklılıkları; beyin salınımlar; oksipital korteks; görsel uyarılmış potansiyeller; teta; potansiyeller; dinamik; gama; görev